2010
DOI: 10.1111/j.1365-2672.2009.04500.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of symbiotic genes and characterization of functional traits of Mesorhizobium spp. strains associated with the promiscuous species Acacia seyal Del.

Abstract: Aims:  To assess the phenotypic, symbiotic and genotypic diversity scope of Mesorhizobium spp. strains associated with Acacia seyal (Del.) isolated from different agro‐ecological zones in Senegal, and uses of susceptible microbial inoculum in a reafforestation process. Methods and Results:  A polyphasic approach including phenotypic and genotypic techniques was used to study the diversity and their relationships with other biovars and species of rhizobia. The geographical origins of the strains have limited ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
(118 reference statements)
2
26
0
Order By: Relevance
“…The authors demonstrated that these two Acacia species were mainly nodulated by Mesorhizobium plurifarium. Moreover, A. senegal and A. seyal species belong to the same crossnodulation group, as demonstrated by Diouf et al [13] in a study where Mesorhizobium spp. strains isolated from A. seyal were able to nodulate both A. senegal and A. seyal.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The authors demonstrated that these two Acacia species were mainly nodulated by Mesorhizobium plurifarium. Moreover, A. senegal and A. seyal species belong to the same crossnodulation group, as demonstrated by Diouf et al [13] in a study where Mesorhizobium spp. strains isolated from A. seyal were able to nodulate both A. senegal and A. seyal.…”
Section: Introductionsupporting
confidence: 54%
“…Unlike nodulation genes, the nif genes are found in a broad spectrum of phylogenetically unrelated bacteria besides rhizobia. Correlations between the phylogeny of nifH and that of 16S ribosomal RNA (16S rRNA) genes were reported [9], and it was proposed that nifH and 16S rRNA genes share a common evolutionary path [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the investigated nodules contained Bacillus (17.9%), Paenibacillus (12.5%) and Pseudomonas (15.9%) NRE species, together with small numbers of other NRE bacterial genera from the classes Actinobacteria, Alpha-and Betaproteobacteria. Nodulation and nitrogen fixation capacity are characters usually studied in rhizobia research, since they give an indication of the host specificity and nitrogen fixing ability (Perret et al, 2000;Moulin et al, 2004;Diouf et al, 2010). No nodC or nifH gene sequences could be detected among the isolates, indicating an endophytic lifestyle rather than a rhizobial lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…For each test, a control was performed, and inoculation and incubation were performed as described by Diouf et al (2010). The use of various carbohydrates (filter-sterilized, 0.2 µm) by rhizobial was tested on MGS agar plates according to the method described by Mohamed et al (2000).…”
Section: Phenotypic Characteristics Of Rhizobial Strainsmentioning
confidence: 99%